Singapore's heritage landscape changes into a multicultural island city nation - Ahmad, Hamidah (Fakulti Alam Bina, 2015)
Singapore's landscape changes were initiated when the British, headed by Sir Stamford Raffles, first set foot on the island in 1819 and hoisted the British flag. From having a modest beginning, Singapore originated from a Malay island belonging to Johor in the southernmost state of Malaysia and underwent almost two centuries of develompent Island City State of the world. The island's timeline witnesses multi faceted layers of transformation which leads to the Island losing its original heritage of a Malay island. The purpose of the study was to exmine the original heritage of Singapore landscape in its early years, the historical events that followed and identify the driving factors that caused its changes. What remains of the existing original heritage are also reviewed.